The Effect of Task Complexity and Knowledge on Audit Considerations with Experience as a Moderator - Kurniawan, I Gde Fajar; Muawanah, Umi; Setia, Kohar Adi (Riwayat: Educational Journal of History and Humanities, 2025)
Audit judgment practiced by professional auditors has always been an interesting topic in both accounting practice and literature. Given the significance of audit judgment in the field of accounting, it is unsurprising that numerous studies have attempted to identify the factors influencing it. Previous research has yielded varied findings on the impact of task complexity and auditor knowledge on audit judgment. This research aims to examine the effect of task complexity on audit judgment, the impact of auditor knowledge on audit judgment, the moderating effect of auditor experience in the relationship between task complexity and audit judgment, as well as between auditor knowledge and audit judgment. The research adopted a quantitative approach, utilizing a survey process through questionnaires. The study population consisted of auditors from 70 Public Accounting Firms in East Java, as listed in the IAPI Directory 2021. To ensure the appropriateness of the analytical method,, validity, reliability, and descriptive statistics were applied. Statistical research techniques included multiple linear regression analysis using SPSS 26. The findings reveal that task complexity significantly and negatively influences audit judgment, auditor knowledge significantly and positively influences audit judgment, and auditor experience moderates the effects of both task complexity and auditor knowledge on audit judgment.